Tulsi Leaves – Immunity Boosting Herb - Suneetha, W. Jessie; Keerthana, A. Gnana; Kumar, J. Hemantha; Kumari, B. Anila; Chaitanya, V.; Kumar, K. Ravi; Akhila, A. (Chronicle of Bioresource Management, 2021)
The global pandemics are due to modern lifestyle, associated lack of physical activity, high intake of processed foods containing more of sugars, fat, salt, consumption of alcohol, smoking and exposure to a toxic cocktail of chemicals. The solution to the current health crisis can be found at homes with dietary changes in humans. ‘Ayurveda’ focuses on healthy lifestyle practices and regular consumption of adaptogenic herbs used for centuries in traditional methods of healing that were long forgotten but with renaissance now. Traditionally, tulsi (Ocimum sanctum Linn) has incredible therapeutic value due to its restorative activities like adaptogenic, antimicrobial, anti-inflammatory, cardioprotective and immunomodulatory effects. High concentration of eugenol in tulsi may act as a COX-2 inhibitor similar to modern day painkillers. It is especially effective in supporting the heart, blood vessels, liver and lungs for regulating blood pressure, blood sugar levels and body’s overall defense mechanism.